Listeria monocytogenes meningoencephalitis in an immunocompetent adult patient - João Daniel Melo; Sara Ventura; Paula Coutinho; Adriano Rodrigues (Sociedade Galega de Medicina Interna, 2016)
Listeria monocytogenes infections may lead to a severe and potentially lethal disease. This occurs mainly in risk groups (elderly, immunocompromised and newborns). Severe infections in people without any of these factors are rare. Here is reported the case of a 24-year old previously healthy female patient, who presented with altered mental status (Glasgow Coma Scale score of 11, with worsening to 6 within a few hours), fever and meningeal signs. The cerebrospinal fluid analysis was compatible with lymphocytic meningitis. Empirical therapy with Ceftriaxone and Acyclovir had been started. There was clinical worsening, with rhombencephalitis viewed in MRI. Ampicilin was associated and Listeria was actively searched, turning out positive. Despite all measures, the patient died in the Intensive Care Unit. This report of a Listeria monocytogenes infection in a patient without risk factors reinforces the need of an early detection and effective treatment.